Payment by environmental service: Analysis of the potential for the region of Angra Doce paranaense, Brazil - Scarpin, Beatriz Piatto; Freiria, Rafael Costa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
The current environmental crisis and intense degradation of natural capital make it increasingly evident the importance of including solutions for the conservation and recovery of ecosystems, such as the Payment for Environmental Services (PES). With an interdisciplinary character and survey of quantitative and qualitative data, the research carried out an evaluation of the ecosystem services and the potential of implementing a PES program in the region of Angra Doce, Paraná, Brazil, which is classified as a Special Area of Tourist Interest and is be listed as a priority area in accordance with the National Payment Policy for Environmental Services (PNPSA). From the results obtained, the region demonstrated that it has the potential to create municipal public policies for PES based on the cultural services established in the guidelines of the PNPSA an experience that can also be used by other Brazilian municipalities.